2017
DOI: 10.2147/opth.s119343
|View full text |Cite
|
Sign up to set email alerts
|

Corneal thickness in dry eyes in an Iraqi population

Abstract: BackgroundDry eye disorder is a multifactorial disease of the tears and ocular surface that results in discomfort and visual disturbance. Corneal pachymetry becomes increasingly important in refractive surgery, for the accurate assessment of intraocular pressure, and in the preoperative assessment of other ocular surgeries.PurposeTo assess the effect of dry eye disorder on the central corneal thickness (CCT) by comparing with CCT of normal eyes of age-matched individuals.Patients and methodsThe total number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…Thirdly, apparently low IOP in summer might be caused by corneal thinning 36 . The central corneal thickness decreases in DED 37 and contributes to low IOP in summer, since measured IOP might be lower than the actual value. Ophthalmologists should be also aware that perimetric results could thus be overestimated in summer 38 because the sensitivities in summer were 0.2 dB below those of winter/spring.…”
Section: Discussionmentioning
confidence: 92%
“…Thirdly, apparently low IOP in summer might be caused by corneal thinning 36 . The central corneal thickness decreases in DED 37 and contributes to low IOP in summer, since measured IOP might be lower than the actual value. Ophthalmologists should be also aware that perimetric results could thus be overestimated in summer 38 because the sensitivities in summer were 0.2 dB below those of winter/spring.…”
Section: Discussionmentioning
confidence: 92%
“…This is paradoxical since if IOP increases with worsening of DED in the cold and dry weather of winter, IOP in short BUT should be higher than in normal BUT for all seasons. A possible explanation for this seeming anomaly is cornel thinning and drug penetration facilitated by disruption of the ocular surface barrier effects in DED, as previous investigations have suggested that IOP estimated as a lower value in thin cornea and intraocular drug effects of instilled eye drops depends on the drug penetration [12,41,42]. Sleep disorder, depression, and possible decreases in melatonin secretion could also contribute to the dysregulation of IOP [21,[23][24][25] in winter when sunshine decreases and DED patients suffer more stress and worsened symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Desiccation stress and amplified inflammatory response in dry eye significantly alters the thickness of the central and peripheral cornea contributing to corneal thinning [ 64 ]. The imbalance between the matrix metalloproteinases (MMPs) and the inhibitors of MMPs significantly degrade the extracellular matrix of the collagenous stroma resulting in corneal thinning [ 65 , 66 ]. Deterioration of the tear film can result in irregular corneal surface that affects the visual quality.…”
Section: Ocular Surface Microenvironment Change In Dry Eyementioning
confidence: 99%